Phycoemotional state of the patients with severe acne associated with isotretinoin therapy - M. L. Aripova; S. A. Khardikova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Progression of phycoemotional state of 22 patients with severe acne was assessed based on changes in rates of CADI, APSEA, DSQL. Monotherapy with isotretinoin (Acnecutan) is effective in treating severe acne resistant to therapy providing stable remission which is shown by decrease in rates of CADI, APSEA, DSQL.